Refluks Laringofaring - Aulia, Wita (SCRIPTA SCORE Scientific Medical Journal, 2020)
Laryngopharyngeal reflux (LPR) is a disease in which retrograde flow occurs from the contents of the stomach to the larynx and pharynx and then this material is in contact with the upper esophagus. This disease is different from gastroesophageal reflux disease (GERD). A man, 58 years old laborer, came with complaints of hoarseness since 3 months ago. Complaints are accompanied by swallowing pain and throat pain that has worsened since 1 month. The patient also complained that the sound had disappeared within 1 month. The patient has a history of smoking and claims that he has had a long-standing heartburn. Physical examination found blood pressure of 150/90 mmHg, pulse 102 x/minute, breathing 20 x/minute, temperature 37.9ºC. Investigations were done using the Fiber Optic Laryngoscope (LFO) and revealed a rigid epiglottis and bilateral hyperemic arytenoids and minimal edema. RSI score calculation results have been 18 and RFS score results have been 9. This pateint’s diagnosis is Laryngopharyngeal reflux (LPR). Pharmacological management for this patient is Omeprazole 40 mg 2x1 tablet, Sucralfate syrup 3x1 teaspoon, and N-acetylcysteine 3x1 tablet. Non-pharmacological management is by telling the patient to give 2 hours time between eating and lying down. The patient is also told to reduce the consumption of fatty foods, coffee, soda, alcohol, and low-acid diets, and position the head slightly higher when lying down. Keywords: Fiber Optic Laryngoscope, laryngopharyngeal reflux, Reflux Finding Score, Reflux Symptom Index     Refluks laringofaring adalah penyakit dimana terjadi aliran retrograde dari isi lambung ke laring dan faring kemudian cairan ini bersentuhan dengan saluran esofagus bagian atas. Penyakit ini berbeda dengan gastroesophageal reflux disease (GERD). Seorang laki-laki, usia 58 tahun seorang buruh datang dengan keluhan suara serak sejak 3 bulan yang lalu. Keluhan disertai dengan nyeri menelan dan nyeri tenggorokan yang memberat sejak 1 bulan ini. Pasien juga mengeluhkan suara sempat hilang timbul dalam 1 bulan ini. Pasien memiliki riwayat merokok dan mengaku bahwa menderita sakit maag sejak lama. Pemeriksaan fisik didapatkan tekanan darah 150/90 mmHg, nadi 102 x/menit, pernapasan 20 x/menit, suhu 37,9ºC. Pada pemeriksaan penunjang Fiber Optic Laryngoscope (LFO), didapatkan epiglotis yang kaku serta aritenoid hiperemis bilateral dan edema minimal. Pada perhitungan skor RSI didapatkan hasil 18 dan skor RFS didapatkan hasil 9. Diagnosis pada pasien ini adalah refluks laringofaring. Penatalaksanaan pada pasien berupa medikamentosa yaitu Omeprazole tablet 40 mg 2x1 tablet, Sukralfat syrup 3x1 sendok teh, dan N-asetilsistein 3x1 tablet. Non-medikamentosa dengan memberitahukan kepada pasien untuk jarak makan dan berbaring kurang lebih 2 jam, mengurangi konsumsi makanan berlemak, kopi, soda, alkohol, dan diet rendah asam, serta memberitahukan kepada pasien untuk memposisikan kepala sedikit lebih tinggi saat berbaring Kata kunci: Fiber Optic Laryngoscope, refluks laringofaring, Reflux Finding Score, Reflux Symptom Index